The effect of socio-economic status on adherence to Anti-retroviral therapy (International Journal of Biomedical and Advance Research, 2015)
Background: Human Immunodeficiency Virus infection is a pandemic disease threatening public health for decades now. With the advent of antiretroviral drugs (ARDs) being taken on long term basis, it is important to examine factors that could affect adherence to these medications Objectives: To determine relationship between socio-economic status of sero-positive HIV patients on antiretroviral drugs and their adherence to these drugs Methods: This is a descriptive cross sectional study. One hundred and fifty patients on ARDs attending retroviral treatment clinic were recruited into the study. Multistage sampling technique was employed in sample selection. Research instrument was semi-structured interviewer administered questionnaires, and data was managed using the SPSS 17 software. Results: There was no statistically significant association between socio-economic status in both sexes (p=0.58). There was a statistically significant comparison between socio-economic status and educational status of respondents (p=0.001). Low income group and retired individuals adhere more with their medications. Respondents with lower socio-economic status are twice more likely to adhere with the use of ARDs compared to those of higher socio-economic status. Conclusion : In the absence of financial implication, patients with low socio-economic status adhered more to ARDs compared to those of higher socio-economic status.